Level of knowledge on low-dose CT lung cancer screening in Sichuan province, China: a cross-sectional study. Issue 9 (20th September 2022) - Li, Ruicen; Luo, Li; Tao, Wenjuan; Huang, Wenxia; Bao, Ting
Abstract : Objectives: Low-dose CT (LDCT) can help determine the early stage of lung cancer and reduce mortality. However, knowledge of lung cancer and lung cancer screening among community residents and medical workers, and potential factors that may affect medical institutions to set up LDCT are limited. Design: A cross-sectional study was conducted in Sichuan province, China, in 2021. Community residents, medical workers and medical institutions were randomly selected, and participants responded to related questionnaires. Knowledge of lung cancer and LDCT lung cancer screening was evaluated. Data analyses were performed using SAS V.9.4. Results: A total of 35 692 residents, 6350 medical workers and 81 medical institutions were recruited; 4.05% of the residents were very familiar with lung cancer and 37.89% were (completely) unfamiliar. Characteristics, such as age and level of education, were significantly related to residents who were very familiar with lung cancer. Furthermore, 22.87% of the residents knew that LDCT can effectively screen for early-stage lung cancer, which was correlated with smoking (OR 1.1300; 95% CI 1.0540 to 1.2110; p=0.006) and family history of cancer (OR 1.2210; 95% CI 1.1400 to 1.3080; p<0.0001); 66.06% of medical workers believed that LDCT can detect early-stage lung cancer. Technicians and nurses were less knowledgeable than doctors about whether LDCT can effectively screen for early-stage lung cancer (OR 0.6976; 95% CI 0.5399 to 0.9015; p=0.0059 and OR 0.6970; 95% CI 0.5718 to 0.8496; p=0.0004, respectively). Setting up LDCT in medical institutions was related to grade, administrative rank, number of hospital beds that opened and total number of medical workers. Conclusions: The knowledge of lung cancer in residents is relatively low, and the knowledge of LDCT in screening (early-stage) lung cancer needs to be improved both in residents and medical workers. Possible factors that affect medical institutions to set up LDCT may need to be incorporated.